APPLYING MEMRISE APP TO IMPROVE STUDENT’S VOCABULARY IN ONLINE LEARNING DURING THE COVID 19 PERIOD AT JOYKIDS PRIVATE LESSON - Kasa, Dessy Natalia (Journal of Education and Research, 2022)
This study aims to apply the Memrise application to improve vocabulary learning for joykids private lesson students on learning during the pandemic. This research is qualitative descriptive research. This research was conducted at Joykids Private lesson in Surabaya. The research subjects were 8 Joykids Private lessons from grades 3 to 5 with beginner English skills. The instruments used are observation, documentation, and interviews. Data collection techniques in this study are data reduction, triangulation, and concluding. The results showed that the ability of students after learning to increase vocabulary through the application was excellent and helped students in increasing English vocabulary during the pandemic. Research shows that this Memrise application-based research is a valuable method for improving students' vocabulary with a fun way of learning.